2008
DOI: 10.3748/wjg.14.6204
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen breath test for the diagnosis of lactose intolerance, is the routine sugar load the best one?

Abstract: Most patients with a positive HBT-25 normally absorb a lower dose of lactose and a strict lactose restriction on the basis of a "standard" HBT is, in most instances, unnecessary. Thus, the 25 g lactose tolerance test should probably be substituted by the 12.5 g test in the diagnosis of LI, and in providing dietary guidelines to patients with suspected lactose malabsorption/intolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…However, there have been studies in India (49) and elsewhere (46,(50)(51)(52) that have used lower lactose doses (20 or 25 g) and found that these are acceptable doses for determining LM; all of these studies used lactose HBT. Because a 50-g dose is considered nonphysiologic, we used 25 g in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…However, there have been studies in India (49) and elsewhere (46,(50)(51)(52) that have used lower lactose doses (20 or 25 g) and found that these are acceptable doses for determining LM; all of these studies used lactose HBT. Because a 50-g dose is considered nonphysiologic, we used 25 g in the present study.…”
Section: Discussionmentioning
confidence: 96%
“…In an Italian study on 20 healthy subjects, a rise in breath hydrogen greater than 20 ppm was less frequent with 12.5‐g lactose than with 25‐g and 50‐g (7/20, 35% vs 13/20, 65% and 15/20, 75%, respectively) . In another study from Italy, of 90 patients with positive LHBT using 25‐g lactose, only 16 (17.7%) was positive with 12.5‐g dose . However, limitations of these studies include small sample size, lack gold standard for diagnosis of LM, and inadequate study design to evaluate effect of milk and its product withdrawal on symptoms in relation to diagnosis of LM with different doses of lactose.…”
Section: Discussionmentioning
confidence: 99%
“…18 In another study from Italy, of 90 patients with positive LHBT using 25-g lactose, only 16 (17.7%) was positive with 12.5-g dose. 17 However, limitations of these studies include small sample size, lack gold standard for diagnosis of LM, and inadequate study design to evaluate effect of milk and its product withdrawal on symptoms in relation to diagnosis of LM with different doses of lactose. Moreover, the phenotype of the subjects was not adequately characterized in some of these studies using standard method such as Rome criteria.…”
Section: Discussionmentioning
confidence: 99%
“…In both periods, all patients underwent a lactose tolerance test with the usual procedure. H 2 concentrations were measured in parts per million (ppm) by means of a Quintron Model DP Microlyzer gas chromatograph every 30 min for a total duration of 4 h after an oral load of 25 g lactose [8]. Patients who did the test in 1997–1998 were only prescribed 12-hour fasting, whereas patients in 2007–2008 were also asked to follow a low-carbohydrate diet written in instructions provided to the patients.…”
Section: Methodsmentioning
confidence: 99%